Urinary and Fecal Diversion Following Pelvic Exenteration: Comparison of Double-Barrelled and Plain Wet Colostomy - Yazici, Sertac; Tonyali, Senol; Bozaci, Ali Cansu; Haberal, Hakan Bahadir; Hamaloglu, Erhan; Ozen, Haluk (Urology Journal, 2018)
Purpose: To assess early and late-term outcomes of patients who had undergone pelvic exenteration and simultaneous fecal and urinary diversion with plain wet colostomy (PWC) or double-barrelled wet colostomy (DBWC). Materials and Methods: The medical records of all patients who had undergone pelvic exenteration and urinary diversion between 2006 and 2017 at our hospital were reviewed retrospectively. Results: In total, 15 patients with a mean age of 56 ± 13 years were included in the study. Simultaneous urinary and fecal diversions were carried out as PWC (n = 8), or DBWC (n = 7). No significant differences were found between PWC and DBWC groups in terms of operation time (373.7 ± 66.5 versus 394.2 ± 133.2 min, P = .955), estimated blood loss (862.8 ± 462.4 versus 726.2 ± 489.4 mL, P = .613), length of hospital stay (13.2 ± 9.1 versus 14.1 ±6.9 days), early complications (25% versus 28.6%, P = 1.0) and late term complications (37.5% versus 42.9%, P = 1.0). The rate of recurrent pyelonephritis in PWC group was higher than DBWC group but not statistically significant (37.5% versus 14.3%, P = .569). Overall survival (OS) of the patients was 385 ± 91 days. There was no difference between OS of patients with PWC and DBWC (414 ± 165 versus 352 ± 70 days, P = .618). Conclusion: PWC and DBWC are valid options for creating simultaneous urinary and fecal diversion after extensive pelvic surgery in patients with short life expectancy. DBWC might be superior to PWC in terms of decreased risk of recurrent pyelonephritis.